(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
The first data about 183 species of lichens and 17 species of lichenicolous fungi of Nature Reserve “Gorgany” (Ukraine) are given. Abrothallus usneae Rabenh. is a new for Ukraine, and species Homostegia piggotii (Berk. & Broome) P. Karst., Lichenostigma gracile Calat., Nav.-Ros. & Hafellner, Micarea cinerea (Schaer.) Hedl., Sphaerellothecium parmeliae Diederich & Etayo, Stigmidium fuscatae (Arnold) R. Sant., Tephromela grumosa (Pers.) Hafellner & Cl. Roux are new for Ukrainian Carpathians. The locations, ecology and notes to each species are presented.